PEMBELAJARAN SOMATIS AUDITORI VISUAL DAN INTELEKTUAL (SAVI) UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK ELEKTRO IKIP PGRI PADA MATA KULIAH RANGKAIAN ELEKTRONIKA - Agus Hari Wibowo (Jurnal Pendidikan, 2012)
The grand  mision  of vocational  school  policy  is to produce graduates  who have national, regional  and international  competitive advantage.  To guarantee  the students of vocational  school sufficient learning  process,  the vocational  school  teacher  traning  institution  is obliged   to   provide   the   qualified    lecturers,    infrastrustures    and teaching  aids and materials.  Among  those requirements,   students  of vocational  school teacher  training  institution  should also be trained in such a way that they  are skillful  in handling  students  to face the working   environment.   This  research   is  attempted   to  meet  such demand   by  developing   teaching   process   under  Somatic  Auditiry Visual  and  Intelectual   Approach    (SAVI)   to  train   the   students sensitive against the environment.